The impact of a gain-sharing cost-reflective tariff on waste management cost under incentive regulation: The Italian case - Giacomo Di Foggia; Massimo Beccarello (Jounal of Environmental Management, 2020)
In many European countries, waste tariff systems are being updated to take account of the consolidation of circular economy objectives. We forecast the impact of a gain-sharing cost-reflective tariff on waste management sustainability. The cost-reflective tariff generates an economic surplus for society, while meeting environmental goals. Based on empirical data we developed two scenarios. The baseline scenario formalizes the current Italian tariff scheme, while the intervention scenario includes users' response to a gainsharing policy. By optimizing the tariff structure, society would benefit from a surplus that could be reached setting an asymmetric regulation based on current waste management efficiency level. Our results will potentially be a basis for directing waste management policy as per tariff design
Keywords: Q5; L5; 330; Environmental management; Incentive regulation; Price cap; Waste fee; Waste management; Waste policy